Implementasi Diversi terhadap Anak sebagai Pelaku Tindak Pidana Penganiayaan - Adimas Maharaja Syahadat; Rini Fathonah; Dona Raisa Monica (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
Child abuse is a problem that requires special attention in determining the sanctions that will be borne by the child perpetrator considering that children are a gift from God Almighty whose dignity and honor must be maintained. The methods used in this study are Normative Juridical and Empirical Juridical. The sources of this study were the Head of Sub-unit 1 of the PPA Unit and Lecturers at the Criminal Law Section of the Faculty of Law, University of Lampung. The data obtained were analyzed qualitatively. The results of this study are: (1) The implementation of diversion at the Bandar Lampung Police is in accordance with the provisions contained in Article 7 paragraph (1) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System that at the level of investigation, prosecution, and examination of cases of children, diversion must be attempted, but it has not been running optimally.. (2) The inhibiting factors for the implementation of diversion as a resolution of criminal cases of child abuse at the Bandar Lampung Police are: lack of public trust in the diversion rules, lack of Bapas personnel, difficulty in bringing together the related parties, and several internal and external factors.